An open-label, randomized trial of the combination of IFN-κ plus TFF2 with standard care in the treatment of patients with moderate COVID-19. (October 2020) - Fu, Weihui; Liu, Yan; Liu, Li; Hu, Huiliang; Cheng, Xiaobo; Liu, Ping; Song, Zhigang; Zha, Lijun; Bai, Shimeng; Xu, Tingting; Yuan, Songhua; Lu, Fengru; et al.
Abstract: Background: Epidemic outbreaks caused by SARS-CoV-2 are worsening around the world, and there are no target drugs to treat COVID-19. IFN-κ inhibits the replication of SARS-CoV-2; and TFF2 is a small secreted polypeptide that promotes the repair of mucosal injury and reduces the inflammatory responses. We used the synergistic effect of both proteins to treat COVID-19. Methods: We conducted an open-label, randomized, clinical trial involving patients with moderate COVID-19. Patients were assigned in a 1:1 ratio to receive either aerosol inhalation treatment with IFN-κ and TFF2 every 24 h for six consecutive dosages in addition to standard care (experimental group) or standard care alone (control group). The primary endpoint was the time until a viral RNA negative conversion for SARS-CoV-2 in all clinical samples. The secondary clinical endpoint was the time of CT imaging improvement. Data analysis was performed per protocol. This study was registered with chictr.org.cn, ChiCTR2000030262. Findings: Between March 23 and May 23 of 2020, 86 COVID-19 patients with symptoms of moderate illness were recruited, and 6 patients were excluded due to not matching the inclusion criteria (patients with pneumonia through chest radiography). Among the remaining 80 patients, 40 patients were assigned to experimental group, and the others were assigned to control group to only receive standard care. Efficacy and safety were evaluated for both groups. The time of viral RNA negative conversion in experimental group (Mean, 3·80 days, 95% CI 2·07–5·53), was significantly shorter than that in control group (7·40 days, 95% CI 4·57 to 10·23) ( p = 0.031), and difference between means was 3·60 days. The percentage of patients in experimental group with reversion to negative viral RNA was significantly increased compared with control group on all sampling days (every day during the 12-day observation period) ( p = 0·037). For the secondary endpoint, the experimental group had a significantly shorter time until improvement was seen by CT (Mean 6·21 days, N = 38/40, 95% CI 5·11–7·31) than that in control group (8·76 days, N = 34/40, 95% CI 7·57–9·96) ( p = 0.002), and difference between means was 2·55 days. No discomfort or complications during aerosol inhalation were reported to the nurses by any experimental patients. Interpretation: In conclusion, we found that aerosol inhalation of IFN-κ plus TFF2 in combination with standard care is safe and superior to standard care alone in shortening the time up to viral RNA negative conversion in all clinical samples. In addition, the patients in experimental group had a significantly shortened CT imaging improvement time than those in control group. This study suggested that this combination treatment is able to facilitate clinical improvement (negative for virus, improvement by CT, reduced hospitalization stay) and thereby result in an early release from the hospital. These data support the need for exploration with a large-scale trial of IFN-κ plus TFF2 to treat COVID-19. Funding: Funding was provided by the National Natural Science Foundation of China, National Major Project for Control and Prevention of Infectious Disease in China, Shanghai Science and Technology Commission, Shanghai Municipal Health Commission.